2020
DOI: 10.1038/s41598-020-58913-8
|View full text |Cite
|
Sign up to set email alerts
|

Soil properties explain tree growth and mortality, but not biomass, across phosphorus-depleted tropical forests

Abstract: We observed strong positive relationships between soil properties and forest dynamics of growth and mortality across twelve primary lowland tropical forests in a phosphorus-poor region of the Guiana Shield. Average tree growth (diameter at breast height) increased from 0.81 to 2.1 mm yr −1 along a soil texture gradient from 0 to 67% clay, and increasing metal-oxide content. Soil organic carbon stocks in the top 30 cm ranged from 30 to 118 tons C ha −1 , phosphorus content ranged from 7 to 600 mg kg −1 soil, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
67
1
6

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 99 publications
(78 citation statements)
references
References 65 publications
4
67
1
6
Order By: Relevance
“…Similarly, older rubber plantations with bigger trees generally had better soil health. This finding is generally consistent with what has been found in other regions reporting the effects of forest biomass on soil properties [41]. However, our observation that actinomycete counts (ACT) were actually higher in older rubber plantations (15 to 25 years) than any of the natural forest types was entirely unexpected.…”
Section: Variation In Soil Health Parameters By Vegetation Typessupporting
confidence: 93%
“…Similarly, older rubber plantations with bigger trees generally had better soil health. This finding is generally consistent with what has been found in other regions reporting the effects of forest biomass on soil properties [41]. However, our observation that actinomycete counts (ACT) were actually higher in older rubber plantations (15 to 25 years) than any of the natural forest types was entirely unexpected.…”
Section: Variation In Soil Health Parameters By Vegetation Typessupporting
confidence: 93%
“…Hence, our findings point to the proposed positive relationship between resource availability and plant species richness via soil resource-based niche differentiation 15,23 . For instance, studies conducted in Africa 40 and Guyana 41 found that belowground soil properties accounted for the variability in aboveground forest structure because differences in resource availability and nutrient retention determined forest dynamics due to different life-history strategy of tree species adapted to different positions along environmental gradients 42 . Such shifts in taxonomic and functional species composition along topoedaphic gradients 35,36 likely reflect trade-offs among investment strategies along the plant economics spectrum 18,43 .…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that the height-diameter relationship varies significantly with climate (Banin et al 2012); soil fertility (Soong et al 2020) and climatic zones (Nogueira et al 2007), forest types and region (Banin et al 2012). As such, the same tree species growing in different sites might have different biomass in the forests.…”
Section: Discussionmentioning
confidence: 99%
“…As such, the same tree species growing in different sites might have different biomass in the forests. Since climate variation and soil fertility affects tree growth (Soong et al 2020), the inclusion of the tree height in developing allometric models improves the accuracy of biomass estimations of forests. The relation between DBH and AGB demonstrates a high coefficient of determination in the linear regression.…”
Section: Discussionmentioning
confidence: 99%